Идентификация изменения температуры пламени при воздействии его на строительные конструкции - Мацевитый, Ю.М.; Слесаренко, А.П.; Сафонов, Н.А. (Видавничий дім "Академперіодика" НАН України, 2008)
An inverse heat conduction problem on determining the influence of the flame temperature on building constructions during a conflagration has been solved according the thermophysical experimental data on the base of the combined use of the straight lines method, method of iterations, structure and variation methods. Results of solving the nonlinear transient radiant heat transfer problems are obtained for each instant in the form of functional series in basis functions, coefficients of which are determined by means of the spline method as time functions of the flame temperature. Variations of the time-dependent flame temperature and the temperature fields in rectangular building columns have been determined.